Coalescence Characteristics of Side‐by‐Side Growing Bubbles in Carboxymethyl Cellulose Solutions. Issue 2 (14th November 2019) - Fan, Wenyuan; Du, Mengqi; Sun, Yawei; Chen, Hui
Abstract: New experimental data are presented on the coalescence dynamics of twin bubbles at two adjacent nozzles in carboxymethyl cellulose (CMC) solutions. The coalescence process was recorded by using a fast video technique and the images were then analyzed to evaluate the regime, efficiency, and patterns of bubble coalescence. The results reveal that the coalescence process contains the four periods of spherical expansion, rapid mergence, overall growth, and instant departure. The coalescence efficiency always passes through five stages with the gas flow rate; it grows with the CMC solution concentration, but decreases with the surfactant concentration, except at very low gas flow rates. The bubble coalescence pattern strongly depends on the nozzle spacing, but conditionally on the gas flow rate and the solution properties. Abstract : Bubble coalescence in non‐Newtonian fluids is essential in designing and optimizing gas‐liquid contactors. The coalescence regime, efficiency, and patterns between bubbles from adjacent nozzles are investigated by taking into account the influences of various factors, such as the nozzle spacing, the gas flow rate, and the solution properties.